Dual models of persuasion in an analysis of religious and moral communication - Krok, Dariusz (Studia Psychologica: Theoria et praxis, 2006)
Most persuasion research since the mid-1980s has been based on theories that incorporate the assumptions of the cognitive response approach about active and effortful processing, but also include hypotheses about persuasion effects derived from effortless processing. These dual models of persuasion are the Elaboration Likelihood Model (ELM) and the Heuristic-Systematic Model (HSM). They provide a framework for understanding the moderation and mediation of persuasive effects, and explain processes that lead to attitude changes. The models seem to be an appropriate methodological tool to analyze religious and moral communication. The study was performed on a group of 398 people, aged 19-26. Having been randomly divided into four groups they listened to one of four different messages containing religious and moral information, and then filled in a questionnaire measuring cognitive responses, evaluation, and understanding. The results showed that religious involvement plays a crucial role in processing religious and moral messages. Interesting interactions suggested that high involvement subjects were processing both the verbal and vocal content extensively, while low involvement subjects did not elaborate message content but followed the peripheral route to persuasion. Vocal cues served as an argument for the former and as a peripheral cue for the latter.